Avaliação do efeito leishmanicida in vitro e in vivo de constituíntes químicos ativos derivados de plantas medicinais - Teixeira, Maria Jania (1999)
Antimonials, drugs of choice for the treatment of leishmaniasis, provide good results but have side effects and cases of resistance have been reported. In recent years, there has been an increase in the search for new antiparasitic drugs developed from plants extracts. This study aims to evaluate the leishmanicidal effects, both in vitro and in vivo, of two chemicals isolated from medicinal plants, tymol and lapachol, and compare that effect with the one obtained by antimonials. As well as to compare the results obtained in vitro with the therapeutical response in vivo. These compounds (0,008 to 4,0mg/ml) were evaluated in vitro against intracellular amastigotes of Leishmania (Viannia) braziliensis (LVb), then tested in an animal model (hamster) to confirm the leishmanicidal activity. In vitro, both tymol and lapachol, exhibited an anti-amastigote effect whereas in vivo these substances were not able to stop the development of LVb-induced lesions in the concentrations of 14mg/kg/day/i.m and 300mg/kg/day/p.o, respectively. These results suggest that they might be getting transformed into non-active metabolite(s) or is neutralized, losing their leishmanicidal activity. The antimonials demonstrated efficacy in vitro as well in vivo. But, in spite of presenting a significant anti-amastigote effect in vitro for LVb and apparent clinical cure in vivo, these drugs (60mg/kg/day/i.m) could not completely eradicate the parasites from the tissues of LVb-infected animals. In the histopathological findings disclosed that, lapachol induced a severe lymph node necrosis and apoptosis, although it didn’t reduce the parasitic load in that site. We also found out the spleen and lymph node respond differently to Leishmania infection, since in the spleen an intense withe pulp hypoplasia occurred whereas in the lymph node a remarkable follicular hyperplasia was the rule. LVb-induced tegumentary leishmaniasis in the hamster showed an unresolved pattern of infection, characterized by lymphadenopathy, hepatosplenomegaly, weight loss and absence of granulomas in the lymph node and spleen. Since the substance effects were not similar in the two models studied, in vitro and in vivo, the in vivo model appears to better reflect the therapeutic potencial of the drugs, therefore being more adequate for the screening of new substances for the treatment of leishmaniasis.